INTEGRATING SERVICE LEARNING IN HIGHER EDUCATION FOR ENHANCED ENVIRONMENTAL CONSCIOUSNESS IN YAN, KEDAH (Journal of Governance and Development (JGD), 2024)
The Service-Learning Malaysia (SULAM) initiative is a credit-bearing program that focuses on experiential learning to enable students to work with faculty to solve community problems using the knowledge and skills they gained from their academic disciplines. SULAM projects carried out for the Environmental Administration Group A course in the Development Management Program at Universiti Utara Malaysia (UUM) during Semester A222 were conducted in collaboration with the community in the district of Kampung Singkir Darat, Yan, Kedah. The objective of these projects was to address environmental issues faced by the community. The methodology used in this project was designed based on the data obtained from SULAM activities, which explores various aspects including methods of implementation, evaluation and documentation. The findings of the projects helped to improve the knowledge and skills of the students, enabling them to become exceptional graduates and responsible citizens. However, there were challenges faced during the SULAM projects, including communication barriers and resource constraints. To overcome these challenges, the students and faculty had to come up with creative solutions, such as using technology to communicate with the community and leveraging local resources to complete the projects. Overall, the SULAM initiative serves as a great example of how experiential learning can be used to solve real-world problems and create a positive impact on society.